The Effect of Aerobic Exercise on hsCRP Levels, Before and After Intervention in Obese Young Adults - Rosdiana Rosdiana; Nilam Fitriani; Baktiana Ratna Etnis; Nur Qamariyah; Nursyamsiyah Nursyamsiyah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Overweight and obesity are accumulations of excess fat (globally, regionally, and in organs as ectopic lipids) increasing the risk of health impacts. In Indonesia, childhood obesity has a high prevalence rate. According to the Indonesian Ministry of Health. The number of children aged 5-12 years experiencing overweight problems is 18.8% which consists of the category of fat 10.8% and obesity by 8.8%. Methods: This study is a research with intervention, quasi-experimental research design, to distinguish high sensitivity C-reactive protein (hs-CRP) levels before and after receiving treatment in two groups, namely the control group (the group that did not receive treatment), and the intervention group (the group that performed aerobic exercise). Result: With dietary and aerobic interventions for 4 weeks, no statistically significant differences were found, although the mean hsCRP levels of the subjects decreased from 2.8 to 2.2 mg/l. The results of non-parametric statistical tests with man whitney test obtained (?> 0.05), namely (? = 0.346) indicating that there is no significant effect between aerobic exercise on hsCRP levels in the treatment group and control group with a value of (? = 0.24) before and after aerobic exercise. Conclution: Based on the results of research and discussion, it can be concluded that aerobic exercise can provide sufficient changes to reduce hsCRP levels in obese significantly, although the results of statistical analysis do not provide significant changes. Food recall does not have an impact on sufficient change, but if control and dietary interventions are applied it will provide significant changes, this can be seen in the results of different calorie consumption levels.